2021
DOI: 10.1007/s13399-021-01604-9
|View full text |Cite
|
Sign up to set email alerts
|

Biogas production from anaerobic co-digestion using kitchen waste and poultry manure as substrate—part 1: substrate ratio and effect of temperature

Abstract: The rapidly declining fossil fuels are no longer able to meet the ever-increasing energy demand. Moreover, they are considered responsible for greenhouse gas (GHG) emission, contributing to the global warming. On the other hand, organic wastes, such as kitchen waste (KW) and poultry manure (PM), represent considerable pollution threat to the environment, if not properly managed. Therefore, anaerobic co-digestion of KW and PM could be a sustainable way of producing clean and renewable energy in the form of biog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 67 publications
3
14
0
Order By: Relevance
“…This contributes to lower activity and growth of the methanogens. A similar observation was reported by ( Rahman et al., 2021 ) in his study when he mono-digested Kitchen Waste (KW) where he reported that due to higher food to microorganism ratio resulted in lowering of the methanogenic activity. However, from this study, it was noted that co-digesting FW with WH improved the percentage of methane in biogas.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…This contributes to lower activity and growth of the methanogens. A similar observation was reported by ( Rahman et al., 2021 ) in his study when he mono-digested Kitchen Waste (KW) where he reported that due to higher food to microorganism ratio resulted in lowering of the methanogenic activity. However, from this study, it was noted that co-digesting FW with WH improved the percentage of methane in biogas.…”
Section: Resultssupporting
confidence: 85%
“…The methane percentage from WH was 58% this could be attributed to the inhibition caused by the excess ammonia due to the low C/N ratio of the WH. High amounts of ammonia result in the inhibition of the methanogenic activity of acetotrophic methanogens which are very sensitive to ammonia hence lowering methane production ( Rahman et al., 2021 ). These results are consistent with the observations made by ( Wang et al., 2012 ), when he co-digested rice straw, dairy manure, and chicken manure it was observed that there was an increased methane content under mesophilic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Based on previous research, existing biogas substrates can be classified to include plant waste [21], animal waste [11,22], food waste [23], fruit waste [24,25], and agricultural products [26]. Biogas productivity from these substrates is affected by physicochemical conditions [11] such as feedstock type, pH, temperature, carbonnitrogen content, Chemical Oxygen Demand [COD], fermentation nutritional requirements, Volatile Fatty Acid [VFA], Total Solid (TS) and Volatile Solid (VS) content [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…An experimental work using a batch reactor has been reported for biogas production using sewage sludge and cow dung (Rao and Baral, 2011). It is also found that kitchen waste and poultry manure are potential candidates for biogas production (Rahman et al, 2021). Researchers showed that the AcoD of animal manure and food waste could produce a high amount of methane yield using batch and semi-continuous processes (Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%